Pengaruh Penambahan Crude Tannin pada Sperma Cair Kambing Peranakan Ettawa yang Disimpan Selama 14 Hari terhadap Viabilitas Spermatozoa (The Effect of Crude Tannin Addition to Liquid Semen of Ettawa Crossbred Goat on The Viability of Spermatozoa During 14 - Oktora Dwi Putranti; Kustono (Kustono); Ismaya (Ismaya) (Buletin Peternakan, 2010)
This study was aimed to obtain viability of Ettawa Crossbred spermatozoa into day 14th on with the addition of crude tannin (CT). The design used was one-way completely randomized design with five replications and five treatments. The data of value identified sperm were analyzed descriptively. Sperm quality data were analyzed using one way analysis of variance (ANOVA) and Tukey-W-test procedure. The results showed that the sperm quality characteristics were as the followed: volume 1.4+0.42 ml; pH 6.84+0.27; creamy milk color; consistency thick; motility ++ and concentration (328.8+80.74) x 107/ml semen.  Spermatozoa viability were K0 (control) 29.89+16.52%; K1 (CT 2.5%) 65.33+8.95%; K2 (CT 5%) 58.20+12.4%; K3 (CT 10%) 52.61+15.34%; and K4 (CT 20%) 47.84+13.84%. It was concluded that the addition of 2.5% crude tannin gave significant effect on viability of Ettawa Crossbred spermatozoa during 14 days storage, whereas addition of 20% crude tannin had caused low percentage of live spermatozoa.(Key words: Spermatozoa, Crude tannin, Viability)